2018
DOI: 10.5536/kjps.2018.45.3.167
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Processed Pine Needle Powder in Broiler Chicken Diets

Abstract: This study examined the effects of dietary processed pine needle tree powder (PPNP) on growth performance, visceral organ parameters, ileal digestibility, blood metabolites and ileal morphology of broiler chickens for 5-week after hatch. In total, 220 1-day-old male Ross 308 broiler chicks were randomly allocated to 30 pens (seven birds per pen), and each pen was assigned to one of five dietary treatments, a diet without PPNP (control) and diets with 0.5%, 1.0%, 1.5% and 2.0% PPNP. The body weight and feed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In healthy animals, protein synthesis increases along with TP and ALB. In our experiment, serum TP and ALB were higher in the PNE100 group than in the other groups, indicating a more vigorous protein metabolism in the PNE100 group, which was consistent with the results of Kim et al ( 13 ), who found that 1% pine needle powder strengthened the ability of broilers to utilize protein and N nutrients. Khan et al also demonstrated that including 150 mg/kg PNE ameliorated serum TP and ALB concentrations in quails ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In healthy animals, protein synthesis increases along with TP and ALB. In our experiment, serum TP and ALB were higher in the PNE100 group than in the other groups, indicating a more vigorous protein metabolism in the PNE100 group, which was consistent with the results of Kim et al ( 13 ), who found that 1% pine needle powder strengthened the ability of broilers to utilize protein and N nutrients. Khan et al also demonstrated that including 150 mg/kg PNE ameliorated serum TP and ALB concentrations in quails ( 16 ).…”
Section: Discussionsupporting
confidence: 92%
“…Khan et al reported that supplementation of 150 mg/kg PNE enhanced quail growth performance ( 16 ). Similarly, Kim et al illustrated that broilers-fed 2.0% simple processed pine needle powder exhibited decreased overall body weight, average daily gain, average daily feed intake, and improved ileal protein digestibility compared with those of broilers-fed diets containing 0, 0.5, and 1.0% pine needle powder ( 13 ). Consistent with our results, Kothari et al showed that adding 2.5 and 5 mg/kg fermented PNE increased egg mass and egg production ( 17 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation